Distributive Justice Beliefs are Guided by Whether People Think the Ultimate Goal of Society is Well-Being or Power. Issue 6 (2nd November 2019) - Meindl, Peter; Iyer, Ravi; Graham, Jesse
Abstract: Disagreements about how resources should be distributed are often heated, perhaps because people suspect that distributive justice beliefs that clash with their own derive from nefarious motives. In this paper, we consider a less pessimistic explanation for diversity in distributive justice beliefs: such beliefs are influenced by what one considers the primary utility or value of their society in the first place. In five studies ( N  = 21, 515), we demonstrate the existence of two separable types of distributive justice beliefs, one (Equality/need) influenced by a focus on societal well-being, and the other (Equity/merit) by a focus on societal power. These findings lend insight into how growing tensions rooted in resource allocation might be defuzed.